2019
DOI: 10.1007/s10461-019-02489-6
|View full text |Cite
|
Sign up to set email alerts
|

A New Generation of Drug Users in St. Petersburg, Russia? HIV, HCV, and Overdose Risks in a Mixed-Methods Pilot Study of Young Hard Drug Users

Abstract: Russia has a widespread injection drug use epidemic with high prevalence of HIV and HCV among people who inject drugs (PWID). We conducted a mixed methods study of young (age 18–26) hard drug users in St. Petersburg. Thirty-nine structured and 10 semi-structured interviews were conducted. No HIV cases and two HCV cases were detected among the PWID subsample (n=29). Amphetamine and other stimulants were common (70%), opioid use was rare and episodic. Consistent condom use was 10%. No PWID reported syringe-shari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 62 publications
1
9
0
Order By: Relevance
“…While in developed countries such as the USA, the HIV infection rate among this population had decreased from 12% in 2006 to 6% in 2018 [ 31 ]. In addition, increasing HIV epidemics were reported among stimulants users in different populations in the USA, Russia and other countries, and a similar trend is also observed in our study [ 32 , 33 ].…”
Section: Discussionsupporting
confidence: 91%
“…While in developed countries such as the USA, the HIV infection rate among this population had decreased from 12% in 2006 to 6% in 2018 [ 31 ]. In addition, increasing HIV epidemics were reported among stimulants users in different populations in the USA, Russia and other countries, and a similar trend is also observed in our study [ 32 , 33 ].…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, the number of needle and syringe exchange programs (NSPs) in Russia has been decreasing since 2010 [11], while opioid agonist therapy (OAT) remains illegal [10]. In addition, harm reduction services were reported to be unattractive to young PWID in Russia [12].…”
Section: Introductionmentioning
confidence: 99%
“…Saint Petersburg is the second largest city in Russia, with a population of approximately 5 million. It has a high concentration of PWID, a critical risk behaviour associated with HIV/HCV acquisition [ 6 ]. An estimated 40,000 PLWH live in Saint Petersburg, with about 2000 new cases diagnosed annually [ 30 ].…”
Section: Methods: Participants Interventions and Outcomesmentioning
confidence: 99%
“…Among HIV-infected women in Saint Petersburg, Russia, a study by our group observed that 57.1% were HCV co-infected [ 4 ]. Behaviours related to injection drug use, such as needle sharing, have contributed to the rapid spread of HIV/HCV co-infection among PWID globally [ 5 ], including in Saint Petersburg, Russia [ 6 8 ].…”
Section: Introductionmentioning
confidence: 99%